A Case of MPO-ANCA Positive Systemic Lupus Erythematosus Developed into Acute Kidney Injury - Suzuki, Satoshi; Ogiwara, Kei; Nishi, Takuya; Sakuma, Shota; Akira, Maiko; Iwasaki, Masako; Honda, Daisuke; Takahara, Hisatsugu; Ikeda, Keigo; Yamaji, Ken; Tamura, Naoto; Rinno, Hisaki; et al. (Archives of Clinical and Medical Case Reports, 2019)
During the course of treatment for rheumatoid arthritis, anti-DNA antibody was detected, and systemic lupus erythematosus was diagnosed, who was subsequently treated with abatacept—and remission was achieved. Rebound of elevated anti-DNA antibody and urinary abnormalities were noted with MPO-ANCA positivity. Renal biopsy revealed lupus nephritis; followed by the development of rapidly progressive glomerulonephritis, which required apheresis (double filtration plasmapheresis) therapy, although no response was achieved. However, plasma exchange therapy was highly effective. These results suggest that MPO-ANCA-positive lupus nephritis can become severe and require intensive treatment in accordance with the treatment for severe vasculitis.